Gambaran Hasil Pemeriksaan Histopatologi Penderita Tuberkulosis Jaringan Lunak di Laboratorium Patologi Anatomi Rumah Sakit Umum Madani Medan Periode 2020-2024 - Hutapea, Risma Ronauli; Lina, Juliana; Lister, Clarissa (Syntax Literate, 2025)
Soft tissue tuberculosis is a rare form of extrapulmonary tuberculosis characterized by Mycobacterium tuberculosis infection of the subcutaneous tissue. This condition is important to recognize because its symptoms are nonspecific and often mimic malignancy, often referred to as a "good imitator." According to WHO data from 2023, the global TB incidence rate was 134 per 100,000 population, with Indonesia ranking second highest in the world. This study aims to describe the results of histopathological examinations of soft tissue tuberculosis patients at Madani General Hospital, Medan, during the period 2020–2024. The method used was a retrospective descriptive study through a review of the medical records of patients examined in the Anatomical Pathology Laboratory. Analysis was conducted on variables such as age, gender, lesion location, and histopathological results. The results showed that the largest age group was 19–27 years (25%), while the smallest was 10–18 years (7.5%). The gender distribution was balanced between males and females (50% each). The most common lesions were the neck and back (22.5%), while rarer locations, such as the axilla, buttocks, mandible, groin, and elbow, occurred in only 2.5% each. All cases were confirmed by histopathology, underscoring the importance of this examination to rule out malignancy and expedite the appropriate management of extrapulmonary tuberculosis.